(untitled) (Veterinary Science, 2019)
One of the drawbacks that usually occurs when working in a veterinary hospital is the need to have a permanent stock of medicines and other health products, including large volumes of sterile parenteral solutions, which are widely used in the daily clinic. Replacement fluids most frequently used are the solutions of dextrose 5 %, sodium chloride 0.9 % and Ringer lactate, among others. It is essential that the solutions to be administered are in sterile conditions. In that sense, short-wave ultraviolet light (UVC), non-ionizing radiation, is a powerful antibacterial agent that disinfects without altering the color, flavor, odor or pH of the sample. The objective of this work was to study the application of UVC radiation to sterilize parenteral solutions with refrigerated storage. We worked with 5 % dextrose solution and 0.9 % physiological solution separated in control samples, untreated, and treated with UVC light. The irradiation dose received by the samples was 3.4095 J/cm2. Subsequently, they were stored in temperature controlled refrigeration chambers at 4 °C for 7 days. It was observed for the case of the irradiated samples, that there was no visible development during that time, conserving its sterility. In addition, the inactivation factor, F.I. %, was determined after 7 days. In both studied solutions , 99 to 100 % inactivation was obtained. Analyzing the obtained results , the use of irradiation with UVC light as a means of sterilization and the subsequent maintenance of the solutions at refrigeration temperatures, we consider that it constitutes an interesting and new technology to be implemented